Combined Antinociceptive Effects of Alpha-Tocopherol and Diclofenac in Acetic Acid-Induced Writhing Test - Juaira, Tasneema; Patwary, Mohammad Asaduzzaman; Begum, Habiba; Afrin, Munira; Salman, Mohammad Nahid; Basak, Puspita (Journal of Monno Medical College, 2026)
Background: The search for effective analgesic combinations with improved efficacy and fewer side effects is an ongoing challenge in pain management. Objective: The purpose of the present study was to determine the combined analgesic efficacy of alpha-tocopherol, a potent antioxidant, and diclofenac, a widely used nonsteroidal anti-inflammatory drug (NSAID), using the acetic acid-induced writhing test in rats. Methodology: This prospective experimental study was conducted in the Department of Physiology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from January to December 2013. 15 male Long Evans rats, weighing 180 to 250 grams, were collected from Bangladesh Institute of Research and Rehabilitation for Diabetic Endocrine and Metabolic Disorders (BIRDEM), Shahbag, Dhaka, Bangladesh for this purpose. On the basis of vitamin and drug administrations, the rats were divided into three 3 groups (5 rats in each). Group A received normal saline, group B received diclofenac sodium, group C received combination of diclofenac sodium with α-tocopherol. All the groups received single dose and equal volume through intraperitoneal route 1 hour before the test. Just one hour after administrations, rats of each group were subjected to the acetic acid induced writhing test. After the completion of experiments, all the rats were sacrificed immediately to decrease their sufferings. Results: This study suggests that combining αT and DS in a single dose may be more beneficial than administering DS alone in reducing nociceptive and inflammatory pain. Conclusion: The results indicate a synergistic interaction between the two compounds, suggesting a potential role for alpha-tocopherol as an adjuvant in pain therapy. Journal of Monno Medical College, June, 2025; 11(1) : 23-27